Coerced Liberation : Muslim Women in Soviet Tajikistan. - Abman, Zamira (Toronto : University of Toronto Press, 2024)
This book offers unique insights into the shifts in behaviour and attitudes surrounding the Soviet emancipation of women in the Muslim periphery, Tajikistan.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books